Efficacy and safety of self-expanding metal stents in patients with inoperable esophageal cancer: a real-life study. - Miguel Jiménez-Gutiérrez, José; Octavio Alonso-Lárraga, Juan; Hernández-Guerrero, Angélica I.; Saul Lino-Silva, Leonardo; Olivas-Martinez, Antonio (Therapeutic Advances in Gastrointestinal Endoscopy)
Background: Dysphagia is the most frequent symptom in patients diagnosed with esophageal cancer. Self-expanding metal stents (SEMS) are the current palliative treatment of choice for dysphagia in patients with non-curable esophageal cancer. This study aimed to evaluate the efficacy and adverse events (AEs) of different types of SEMS for palliation of dysphagia. Methods: We performed a retrospective cohort study of patients with advanced esophageal cancer and SEMS placement for dysphagia palliation in a tertiary care center. The primary outcome was the clinical success defined as an improvement in dysphagia (reduction of at least 2 points in the Mellow-Pinkas scoring system for dysphagia) after SEMS placement. Results: Between January 1999 and May 2020, 295 patients with esophageal cancer were identified. Among them, 75 had a SEMS placement for dysphagia palliation. The mean age of the patients was 61.3 years (standard deviation: 13.4), 69 patients (92%) were men, and the mean Mellow-Pinkas scoring for dysphagia pre- and post-SEMS placement were 3.1 and 1.4 (change from baseline -1.7), respectively. Technical success and clinical success were achieved in 98.6% and 58.9%, respectively. AEs were identified in 35/75 patients (46.7%), and SEMS migration was the most frequent AE in 22/75 patients (29.3%). There were no significant differences in improvement in dysphagia (p = 0.054), weight changes (p = 0.78), and AE (p = 0.73) among fully covered SEMS (fc-SEMS) and partially covered SEMS (pc-SEMS). The median follow-up was 89 days (interquartile range: 29-221). Conclusion: SEMS placement was associated with a rapid improvement in dysphagia, high technical success, and a modest improvement in dysphagia with no major AE among fc-SEMS and pc-SEMS.